Mathematical simulation and optimization of a waste energy recovery for an internal combustion engine integrated with ScCO2 cycle and modified Kalina cycle. (October 2022) - Ibrahim Almohana, Abdulaziz; Fahad Almojil, Sattam; Fahmi Alali, Abdulrhman; Anqi, Ali E.; Rajhi, Ali A.; Alamri, Sagr; Dhahad, Hayder A.; Najat Ahmed, Ahmed; Mohamed, Abdullah
Abstract: In the current research, thermodynamic simulation of a waste heat recovery system (WHRS) for an internal combustion engine (ICE) employing a S c C O 2 cycle, an ORC, and a modified Kalina cycle integrated with a thermoelectric generator is developed. The energy, exergy, and exergo-economic are applied to evaluate the suggested system. An engineering equation solver (EES) code combined with Matlab software is developed to conduct a thermodynamic simulation and multi-objective optimization of the waste heat recovery plant. The results represent in the suggested system the energy efficiency, exergy efficiency, and net output power are 26.33 %, 51.69 %, and 2657 kW, respectively. About 70.5 % of the overall exergy destruction of the proposed system belongs to the heat exchanger 1, generator, thermoelectric 1, and compressor. The economic analysis results show that the thermoelectric 1, ORC turbine, compressor and Kalina turbine have the highest purchase equipment cost in the designed system. Calculations show that the thermoelectric 1, and Kalina turbine have the highest potential for optimization and minimizing their value of relative cost difference. In the parametric analysis, four variables were investigated, which is a base for multi-objective optimization in three schemes. The introduced multi-objective scenarios provide appropriate data for a designer to propose the new waste heat recovery plants.